THE EFFECTIVENESS GEOGEBRA SOFTWARE AS MATHEMATICS LEARNING MEDIA TOWARD MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII AT SMP 2 SUKOHARJO WONOSOBO REGENCY - Samsul Bahri A; Harina Fitriyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Lack of attention of students for teacher’s explanation in learning influence student’s learning outcomes mathematics. One of media learning who focus on student’s attention are using software GeoGebra. The purpose of research to know The Efectivenest Geogebra Software as Mathematics Learning Media  Toward Student Mathematics Learning Outcomes in Class VIII at SMP 2 Sukoharjo of Wonosobo Regency on the Even Semester Of Academic Year 2015/2016. The population in this study were all students of class VIII SMP 2 Sukoharjo Wonosobo Regency on the even Semester Academic Year 2015/2016. Who consists of three class in totally 86 students. This sample research was the VIII D class for experiment class and VIIIC controlling class selected as random sampling for class. The data collection method uses the test method. Instrument research was mathematics learning outcomes. Data analysis used the hypothesis test. The result of research by using 5% extend significantly and the degrees of freedom are 39, that's point are : (1) there differences of mathematics learning outcomes that using software GeoGebra learning media without use software geogebra.it’s pointed in    . In order that  and (2) mathematics learning used software GeoGebra as learning media more effective than learning compared without use software GeoGebra. It’s a point of   in order that   .